Primary Reconstruction of Combined Anorectal and Vaginal Blast Injury in a Pediatric Patient Without Fecal Diversion: A Case Report - Omar Alameddine; Yasmina Salam; George Hatoum; Nathalie Chamseddine; Samir Akel (European Journal of Pediatric Surgery Reports, 2026)
Blast injuries involving the perineum are rare, particularly in the pediatric population, and may result in complex combined anorectal and genitourinary trauma. These injuries present major reconstructive challenges because of contamination risk, infection and possible long-term functional impairment. Management has traditionally favored staged procedures with fecal diversion, especially in severe anorectal and rectovaginal injuries. We report here the case of a 10-year-old girl who sustained a severe blast injury resulting in a large perineal defect involving the anal canal, perineal body and posterior vaginal wall. The patient underwent a successful single-stage reconstruction surgery consisting of posterior vaginal wall repair, perineal body reconstruction and anterior anorectal wall repair without diverting colostomy. She tolerated the procedure well and remained stable throughout the perioperative course. This case adds to the limited pediatric literature on severe perineal trauma and suggests that, in selected hemodynamically stable patients with extraperitoneal injury and viable tissues, primary layered reconstruction without fecal diversion may be feasible.